Nonlinear optical absorption of antimony and lead oxyhalide glasses - Araújo, Renato E. de; Araújo, Cid B. de; Poirier, Gäel; Poulain, Marcel; Messaddeq, Younes [UNESP] (AIP Publishing, 2003)
The optical limiting behavior and nonlinear optical properties of antimony and lead oxyhalide glasses were discussed. The large nonlinear absorption coefficients which range from 11 to 20 cm/GW was determined using standard Z-scan technique. The photodarkening in the samples were observed which suggested that they can also be useful for inscribing Bragg gratings using green lasers of moderate power.
Keywords: Antimony; Laser pulses; Lead compounds; Light absorption; Nonlinear optics; Photochromism; Nonlinear absorptions; Glass